Metabolite Modulation in Human Plasma in the Early Phase of Acclimatization to Hypobaric Hypoxia - Liao, Wen-Ting (Sci Rep, 2016)
The exposure of healthy subjects to high altitude represents a model to explore the pathophysiology of diseases related to tissue hypoxia. We explored a plasma metabolomics approach to detect alterations induced by the exposure of subjects to high altitude. Plasma samples were collected from 60 subjects both on plain and at high altitude (5300 m). Metabolite profiling was performed by gas chromatography-mass spectrometry (GC-MS) and ultra-performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UPLC-QTOFMS) in conjunction with univariate and multivariate statistical analyses. ELISA assays were further employed to measure the levels of several relevant enzymes together with perturbed metabolic pathways. The results showed that hypobaric hypoxia caused significant and comprehensive metabolic changes, as represented by significant changes of 44 metabolites and 4 relevant enzymes. Using MetaboAnalyst 3.0, it was found that several key metabolic pathways were acutely perturbed. In addition, 5 differentially expressed metabolites in pre-exposure samples from the acute mountain sickness-susceptible (AMS-S) group compared with those from the AMS-resistant (AMS-R) group are identified, which warrant further validation as potential predictive biomarkers for AMS-S individuals. These results provide new insights for further understanding the pathophysiological mechanism of early acclimatization to hypobaric hypoxia and other diseases correlated to tissue hypoxia.